Prevalence of hearing loss in a population of schoolchildren with Down syndrome from Bogotá, Colombia. (2020)
Introduction: Children with Down syndrome have a higher prevalence of hearing disorders, secondary to anatomical and physiological variations. No universal hearing screening is implemented in Colombia, so there are no data available on the prevalence of hearing loss in this population. The objective of this study was to determine the frequency and type of such disorders in this population based on hearing tests.Patients and methods: This was a cross-sectional study conducted at two institutions specialized in accompanying and supporting the families of children with Down syndrome in Bogota, D.C., Colombia. Between October 2017 and September 2018, a behavioral and / or pure-tone audiometry and an impedance audiometry were done in 40 and 37 children respectively. Subjects attended the institutions twice a week and were integrated at school, up to fifth grade. Prevalence was estimated and characteristics, clinical history, and language developmental milestones were described.Results: The sample was made up of 40 children (22 girls) aged 6-18 years (mean: 11.23). A history of otitis was found in 19 children and of mild to moderate hearing loss, in 17, predominately conductive. A delay in language developmental milestones was observed, apparently not associated with hearing loss.Conclusions: A sample of children with Down syndrome from Bogota showed a high prevalence of hearing loss, consistent with the results of previous studies. These data stress the need for a strict control of hearing status based on standardized parameters and guidelines.